2020
DOI: 10.1515/med-2020-0164
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in stage I gastric cancer: A retrospective analysis

Abstract: PurposeThe purpose of this research is to investigate the prognostic factors of patients with stage I gastric cancer (GC) and to determine whether adjuvant chemotherapy improves the prognosis for high-risk patients.MethodsWe performed a retrospective analysis at Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, and HwaMei Hospital, University of Chinese Academy of Sciences from January 2001 to December 2015. Cox regression and Kaplan-Meier were used to evaluate the relationship between the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…It is well known that lymph node metastasis was an inescapable prognostic factor that indicated the mode and range of surgery (31,32). The survival markedly decreased with the increase of the lymph nodes metastasis (33)(34)(35). However, Sekiguchi M et al found that the prevalence of LNM was rarely low, about 12.3%, in early gastric cancer(36).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that lymph node metastasis was an inescapable prognostic factor that indicated the mode and range of surgery (31,32). The survival markedly decreased with the increase of the lymph nodes metastasis (33)(34)(35). However, Sekiguchi M et al found that the prevalence of LNM was rarely low, about 12.3%, in early gastric cancer(36).…”
Section: Discussionmentioning
confidence: 99%
“…Nodal involvement (N stage) was one of the prognostic factors for patients eligible for surgery in GC and used in the most commonly applied staging systems (2). It was reported as an independent prognostic factor since there's a close relationship between lymph nodes, tumor stage, and prognosis (14). In our MLN size <1.05 cm group, 48 patients were in the pN1 stage and 7 patients were in the pN3 stage.…”
Section: Discussionmentioning
confidence: 50%
“…Although VI was not associated with postoperative recurrence in some studies which analyzed stage I and T4 GC [ 20 – 22 ], we speculate that it may be due to the intrinsic excellent and dismal prognoses of stage I and T4 GCs, respectively. In fact, many studies concluded that the lymphatic/vascular invasions are not directly related to patients’ prognosis with stage I GC [ 24 ]. The low sensitivity for detecting VI may also underlie the results when VI was assessed by the HE staining.…”
Section: Discussionmentioning
confidence: 99%